The Dynamics of Religious Moderation in The Prevention of Religious Conflict in Multicultural Communities: A Case Study of Pakelan Village, Pancasila Village, Kediri City - Zainura Nada Pertiwi; Desi Fitria Rahmadani (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
Pancasila Village is an area in Pakelan Village, Kediri City. impressively, this village has a lot of different cultures, beliefs, tribes and ethnicities there. Even though there are many differences in the village, they still live in harmony, help each other and if there is a conflict they will resolve it through deliberation. Linguistically, multiculturalism can be understood by understanding many cultures. Culture in the sense of ideology and at the same time as a tool towards the highest level of humanity. So it can be concluded that multiculturalism is an awareness of seeing cultural diversity as an important part of social life. In the Big Indonesian Dictionary (KBBI), the word moderation is defined with two meanings, firstly reducing violence, secondly avoiding extreme behavior , while moderate always means avoiding extreme behavior , and leading to a middle ground dimension. Religious moderation ( wasathiyah ) can be interpreted as an individual's perspective or point of view in taking a fair and non-fanatic stance in making decisions. So, religious moderation is needed in order not to close oneself off, be easy to get along with, interact with, and prevent conflict between religious communities. This article discusses the attitude of residents or the local government to maintain harmony in order to prevent conflicts that occur in Pancasila Village, Pakelan Village, Kediri City.